Exploring self toward expanding teaching, teacher education and practitioner research - Ergas, Oren; Ritter, Jason K. (Emerald Publishing Limited, 2020)
Against the backdrop of a pull toward external standards and accountability, this collection of chapters re-grounds us in the importance of bringing the 'self' to the foreground of the discourse of teaching, teacher education and practitioner research. Showcasing the work of an international group of scholars whose research and teaching in higher education institutions focuses on working with teachers at the intersection of their professional and personal identities, this book explores diverse practices, such as self-study and mindfulness, that examine, evoke and invoke the self. The authors articulate a range of important questions: What do we mean when we speak of 'self' in the domain of teaching, and its research and practice? Why is it important for teachers to explore themselves in an age of high-stakes testing and performativity? Developing explorations of 'self' hat stem from a variety of epistemologies spanning Western and East-Asian philosophical schools of thought, this book delves into a rich journey toward the deep, ancient and ever-present question of who we are, opening up various theoretical and practical methods for advancing the endeavors of teaching and teaching research.
Prelims -- Introduction: Why Explore Self in Teaching, Teacher Education, and Practitioner Research -- Chapter 1 The Calm, Clear, and Kind Educator: A Contemplative Educational Approach to Teacher Professional Identity Development -- Chapter 2 Unleashing the Elephant out of the Closet and into the Wildness of Inner Work -- Chapter 3 The Nature of Self and Its Challenges to Educational Orthodoxy and "Discipline" -- Chapter 4 Working in the Space Between: Conundrums in Self-Study of Practice Research -- Chapter 5 Studying the Self in Self-study: Self-knowledge as a Means Toward Relational Teacher Education -- Chapter 6 The Self in Teaching: An Ecological Approach -- Chapter 7 Unprivileging Dividedness: In Favor of Undivided Ways of Knowing -- Chapter 8 The Educational Self as a Starting Point for Understanding and Self-study in Teaching and Teacher Education -- Chapter 9 The Formation of the "Teaching Self" Through the Pulls of Day-to-Day and Meaning -- Chapter 10 Nature-based Mindfulness and the Development of the Ecological Self When Teaching in Higher Education -- Chapter 11 Two Perspectives on Teaching Mindfulness in Teacher Education: A Self-study of Two Selves -- Chapter 12 The Teaching Self as Productive Embodied Friction: An Account on the Integration between Contemplation and Anti-oppressive Education -- Afterword: Looking Back, Moving Forward.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Reflective teaching; Effective teaching; Self; Education -- Educational Psychology; Educational psychology